2014
DOI: 10.1039/c4sc00462k
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-seamed pyrogallol[4]arene dimers as structural components in a two-dimensional MOF

Abstract: Computational methods were used as a proof of principle in the synthesis of a two-dimensional coordination polymer constructed from zinc-seamed pyrogallol[4]arene dimeric nanocapsules and 4,4′-bipyridine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 26 publications
6
32
0
Order By: Relevance
“…2, atom Zn1 is tetracoordinated by three O-atom donors from two separate TCA 3À ligands, a DMF molecule in a monodentate coordination mode and a pyridine N-atom donor from a bipy molecule, resulting in a slightly distorted tetrahedral geometry. The Zn-O(TCA 3À ), Zn-O(DMF) and Zn-N(bipy) bond lengths (Table 2) are comparable with reported literature values (Chang et al, 2014;Yang et al, 2010;Mossine et al, 2014;Fang et al, 2006). The X-Zn-X (X is a basal O or N atom) angles in the distorted tetrahedron range from 94.70 (4) to 136.29 (1) and the tetrahedron edge lengths range from 2.9998 (4) to 3.6230 (5) Å .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…2, atom Zn1 is tetracoordinated by three O-atom donors from two separate TCA 3À ligands, a DMF molecule in a monodentate coordination mode and a pyridine N-atom donor from a bipy molecule, resulting in a slightly distorted tetrahedral geometry. The Zn-O(TCA 3À ), Zn-O(DMF) and Zn-N(bipy) bond lengths (Table 2) are comparable with reported literature values (Chang et al, 2014;Yang et al, 2010;Mossine et al, 2014;Fang et al, 2006). The X-Zn-X (X is a basal O or N atom) angles in the distorted tetrahedron range from 94.70 (4) to 136.29 (1) and the tetrahedron edge lengths range from 2.9998 (4) to 3.6230 (5) Å .…”
Section: Resultssupporting
confidence: 89%
“…Atom Zn3 is hexacoordinated by four carboxylate O-atom donors from two separate TCA 3À ligands in chelating modes, by another O-atom donor from a DMF molecule and by a pyridine N-atom donor from a bipy molecule. The Zn-O/N bond lengths (Table 2) are comparable with literature values (Chang et al, 2014;Yang et al, 2010;Mossine et al, 2014;Fang et al, 2006).…”
Section: Figuresupporting
confidence: 88%
“…Since the initial discovery by Atwood et al in 2005 35 of PgC n -based MONCs constructed from six PgC n units and 24 Cu 2+ ions, a number of studies have demonstrated that PgC n can self-assemble into octahedral hexameric M 24 (M=Mg, Co, Ni, Cu, and Zn) 36 40 , spherical dimeric M 8 (M=Co, Ni, Cu, and Zn) 41 43 , “rugby ball” shaped hexameric Ga 12 44 or mixed nanocapsules 45 47 . Interestingly, spherical Cu 8 and Zn 8 dimers can be linked by 4,4′-bipyridine ligands into a one-dimensional coordination polymer 48 and an MOF-like structure 49 , respectively. However, PgC n -based MONCs are limited to the aforementioned metal ions, and still have the possibility of synthesizing new PgC n -based MONCs and exerting control over their self-assembly behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a series of nanomaterials have been used in analytical electrochemistry, including gold nanoparticles [ 22 , 23 , 24 ], metal or metal oxide nanoparticles [ 25 , 26 ], quantum dots [ 11 ], graphene [ 14 , 27 ], and metal–organic frameworks (MOFs) [ 28 , 29 ]. MOFs, porous inorganic–organic hybrid materials assembled from metal ions and organic ligands, have attracted attention as a novel material with well-defined porosities, high surface areas, and chemical stability [ 30 , 31 ]. Owing to the excellent characteristics, various biosensors based on MOFs have been developed for detecting heavy metals [ 29 , 32 ], antibiotics [ 33 , 34 ], phosphoprotein [ 35 ], and so on.…”
Section: Introductionmentioning
confidence: 99%